A Prospective Study of Lactate Levels in Uncomplicated Spontaneous and Induced Labor - Kleinmann, Whitney; Zofkie, Amanda; McIntire, Donald; Adhikari, Emily H. (American Journal of Perinatology, 2024)
Objective Maternal pushing can yield lactate levels that are above the normal range for nonpregnant individuals. Many hospitals require lactate levels as part of sepsis bundles, and this can confuse the clinicians when measured during labor. The objective of this study was to observe lactate levels in uncomplicated labor.Study Design This was a prospective study of patients presenting to Labor and Delivery in early labor. Patients met inclusion criteria if they presented at 37 weeks' gestation or greater and were either 3 to 4 cm dilated, in early labor with rupture of membranes less than 12 hours, or were being induced for oligohydramnios or postdates gestation. A baseline maternal lactate level was collected at enrollment. Further levels were collected at complete cervical dilation and every 30 minutes during the second stage of labor up to 3 hours or until delivery.Results From January 7, 2021, through December 30, 2021, a total of 148 screened patients met the inclusion criteria and 38 were enrolled. Eight (21%) patients withdrew after baseline lactate level was drawn. Twenty-three (61%) patients had a level drawn at complete dilation. Of the 12 (32%) patients with a lactate level drawn at complete and after 30 minutes of pushing, the mean change in lactate level was 2.0 ± 1.8 mmol/L or 0.07 ± 0.06 mmol/L/min (p < 0.01). This change is more pronounced in the second stage of labor for patients with chorioamnionitis (2.6 mmol/L), although this difference is not statistically significant (p = 0.41).Conclusion Lactate levels increase significantly once a patient reaches complete cervical dilation within 30 minutes of pushing. This increase is more pronounced, although significantly, in patients with chorioamnionitis. As sepsis is one of the leading causes of maternal morbidity and mortality, this pilot study is relevant for providers to see the natural course of lactate levels in labor.Key Points
Keywords: sepsis; bundle; delivery; infection; morbidity